Sistem Informasi Pendalaman Materi Berbasis Web Pada SMA Cengkareng 1 Menggunakan Model Waterfall - Susafa'ati Susafa'ati; Nunung Hidayatun; Hidayanti Murtina (Computer Science (CO-SCIENCE), 2023)
Cengkareng 1 High school as an educational institution  providing senior secondary education in the city of West Jakarta. In every semester the school always conducts a study evaluation in the form of a written exam. The problem faced by the school is that the school wants to hold a deepening of the material for students to face the exam but is constrained by time, place, cost and teaching staff. From these problems, a system was created that could document the material, assignments and presentation of the questions as part of the implementation of deepening the material. Analysis and design by waterfall method. Research begins with conducting literature reviews, collecting data, analyzing systems and requirements, building system models using UML, designing application implementations, testing using black box testing, and maintaining system data. The results of this research are provided in the form of a web-based material immersion application. The application has the ability to provide materials, monitor student assignment uploads, and help students identify their limitations as they prepare for school and national exams.